Engineered Human Muscle Tissue from Multilayered Aligned Myofiber Sheets for Studies of Muscle Physiology and Predicting Drug Response (Small Methods 2/2023). Issue 2 (17th February 2023) - Takahashi, Hironobu; Wakayama, Haruno; Nagase, Kenichi; Shimizu, Tatsuya
Abstract : Inside Front Cover In article number 2200849, Takahashi and co‐workers report the cell sheet‐based tissue engineering supported production of muscle tissue that replicates muscle physiology in the human body. Since the multilayered human muscle tissue allows us to determine effects of drugs quantitatively, the tissue modeling system has great potential for preclinical drug testing.